2008
DOI: 10.1002/ijc.24071
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulated microRNAs and their predicted targets associated with endometrioid endometrial adenocarcinoma in Hong Kong women

Abstract: The objective of this study, a parallel study to global gene expression profiling, was to identify dysregulated microRNAs (miRNAs) associated with endometrioid endometrial adenocarcinoma (EEC), examine their correlation with clinico‐pathological characteristics and identify predicted target genes of the dysregulated miRNAs. Using real‐time quantitative reverse transcription‐polymerase chain reaction (qRT‐PCR), profiling of miRNA expression was performed in 30 EECs and 22 normal counterparts in which genome‐wid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
144
1
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 145 publications
(155 citation statements)
references
References 35 publications
6
144
1
4
Order By: Relevance
“…10 RNA quantity and quality were assessed with NanoDrop ND-1000 (Thermo Fisher Scientific). A 260 /A 280 nm !…”
Section: Rna Isolationmentioning
confidence: 99%
See 3 more Smart Citations
“…10 RNA quantity and quality were assessed with NanoDrop ND-1000 (Thermo Fisher Scientific). A 260 /A 280 nm !…”
Section: Rna Isolationmentioning
confidence: 99%
“…10 For mRNA quantification, total RNA (5 lg) was reverse transcribed using SuperScript II Reverse Transcriptase (Invitrogen) as instructed. qRT-PCR was done according to the manufacturer's protocol.…”
Section: Quantitative Real-time Pcrmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, miR-205 was shown to be downregulated in advanced-stage PCa in our studies (Figure 1a and 1b) and to be down-regulated in metastatic PCa. 23 Chung et al 24 reported that the aberrant expression of miR-205 took place in advanced stages in endometrial cancer. In addition, previous studies have shown that the level of miR-205 was inversely correlated with PSA and tumor stage.…”
Section: Mir-205 Suppresses Tumor Growth In Vivomentioning
confidence: 99%